Brain endothelial cells‐derived extracellular vesicles overexpressing ECRG4 inhibit glioma proliferation through suppressing inflammation and angiogenesis. (29th September 2021) - Huo, Haoran; Yang, Song; Wu, Haotian; Sun, Yuchen; Zhao, Ranran; Ye, Ruihao; Yan, Dongdong; Shi, Xuefang; Yang, Jiankai
Abstract: Esophageal cancer related gene‐4 (ECRG4) has been shown to be a candidate tumor suppressor in many tumors, but its role in glioma remains poorly understood. This study aimed to explore whether extracellular vesicles (EVs) derived from brain endothelial cells which overexpressed ECRG4 have anti‐tumor effect on gliomas in vivo and in vitro, as well as the possible mechanism. A constructed lentivirus expressing the ECRG4 gene was transfected into the hCMEC/D3 cell line. The EVs were isolated from the cells and characterized by Western blot with exosome markers of CD9, CD63, CD81, Alix. RT‐PCR and Western blot were performed to verify ECRG4 expression. 3‐(4, 5‐Dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide and clone formation assays were applied to detect the proliferation of glioma cells incubated with EVs expressing the ECRG4 (ECRG4‐exo). The level of inflammatory cytokines and angiogenesis related factors, including nuclear factor kappa‐B (NF‐κB), interleukin (IL)‐1β, IL‐6, IL‐8, monocyte chemoattractant protein‐1 (MCP‐1), hypoxia‐inducible factor 1‐alpha (HIF‐1α), vascular endothelial growth factor (VEGF) and vascular endothelial growth factor receptor 2 (VEGFR2) levels were detected by ELISA. The T98G cell xenograft mouse model was established and treated with ECRG4‐EV. The tumor volume and weight were recorded. p38‐MAPK, p‐p38‐MAPK proteins were determined by Western blot in tumor tissues. As a result, EVs can be internalized into U87MG and T98G cells. ECRG4‐EV inhibited U87MG and T98G cell proliferation. ECRG4‐EV also inhibited the expression of factors involved in inflammation and angiogenesis. In addition, ECRG4‐EVs suppressed tumor growth and decreased the production of inflammatory cytokines through inactivation of p38‐MAPK signal pathway. In conclusion, ECRG4‐EVsuppresses glioma proliferation through modulating the inflammation and angiogenesis.